Use of Autologous Stem Cells for the Regeneration of Periodontal Defects in Animal Studies: a Systematic Review and Meta-Analysis - Algimantas Gaubys; Valdas Papeckys; Mindaugas Pranskunas (eJournal of Oral Maxillofacial Research, 2018)
Objectives: To overview preclinical animal trials and quantify the effect size that stem cell therapy has on the regeneration of periodontal tissue complex.